PRESCRIPTIONS OF DOMESTIC WORK PLATFORMS: A COMPARATIVE STUDY BETWEEN BRAZIL AND THE UNITED STATES - Rebechi, Claudia (AoIR Selected Papers of Internet Research, 2026)
The proposal presents partial results of ongoing research about prescriptions of domestic work platforms. Its main objective is to discuss the communication between digital care work platform companies and their workers, considering a comparative approach between organizations operating in Brazil and the USA.Taking advantage of the historical social, gender, race, and class inequalities of both countries, these business organizations are expanding widely and intensively exploiting the care work of people and households carried out by millions of women.In this context, platform companies mobilize different communication uses in support of their logic of management and organization of work. In the case of this proposal, a critical analysis will be presented on domestic work prescriptions identified in the discourses disseminated by digital platform companies in both countries.Specifically, we will deal with the guidelines workers receive from companies to carry out their work. This study involves a theoretical-methodological path that includes bibliographic and documentary research based on Brazilian and North American data, whose results show similarities and differences in domestic work in the platform economy in different Global South and Global North territories.